Illness and injury among Norwegian Para athletes over five consecutive Paralympic Summer and Winter Games cycles: prevailing high illness burden on the road from 2012 to 2020 - Steffen, K.; Clarsen, B.; Gjelsvik, H.; Haugvad, L.; Koivisto-Mørk, A.; Bahr, R.; Moseby Berge, H. (British Journal of Sports Medicine, 2022)
Objective: To describe the illness and injury pattern of Norwegian Para athletes over five consecutive Paralympic Summer and Winter Games cycles and to identify which health problems should be targeted in risk management plans with respect to impairment types.